Model experiment on the dynamic process of oil leakage from the double hull tanker. (September 2016) - Lu, Jinshu; Yang, Zhenbo; Wu, Haoxiao; Wu, Wenfeng; Liu, Fengchen; Xu, Song; Yang, Hao; Yan, Shiqiang
Abstract: This paper presents an experimental investigation on oil leakage from the double hull tanker (DHT). It is designed to explore the dynamic process of oil leakage from bottom-rupture hole of DHT. The experimental test shows the leakage resistance mechanism of ballast tank space. The behavior of oil leakage from damaged DHT and dynamic features of flow in the overall process are demonstrated from experimental results. The overall process of oil leakage is divided into free-leakage and resistance-leakage stage according to the corresponding power to study the dynamic features of oil-water flow inside or outside the tank. The corresponding dominated factors of oil leakage in different stage are also pointed out, and the unsteady Bernoulli's equation is used to verify experimental results. Meanwhile, viscous effect in leakage process is discussed and the importance of hydrodynamic features associated with the mechanism of oil leakage is explored from experimental results. Highlights: Investigation of dynamic process of oil leakage from double hull tanker is presented. Dynamic process of oil leakage is divided in free-leakage stage and resistance stage. The viscous effect is considered in the investigation of dynamic process of oil leakage. The test system is established to investigate dynamic characteristics of oil leakage. The unsteady Bernoulli's equation is applied to verify experimental results.